La nouvelle interlope 2. - Belmont, Charles; Brullé, Pierre; Deckmyn, Nicolas; Fleck, Robert; Giquel, Pierre; Huitorel, Jean-Marc; Labaume, Vincent; Ravalec, Annie-Laurie Le; Raynaud, Patrick; Sipp, Thomas; Strba, Annelies; Tiberghien, Gilles A.; et al. (Nantes : ERBAN - Ecole Régionale des Beaux-Arts de Nantes, 1999)
Duyckaerts, Eric ; Buyse, Alain ; Rivet, Pascal ; Cottencin, Jocelyn ; Soubrane, Bruno ; Heidsieck, Bernard ; Lafontaine, Marie-Jo ; Lebaume, Vincent ; Revalec, Annie-Laurie Le ; Jézéquel, Claire-Jeanne ; Janot, Guillaume ; Cognée, Philippe ; Leroy, Eugène ; Huitorel, Jean-Marc ; Fleck, Robert ; Dijkstra, Rineke ; Ardouvin, Pierre ; Sipp, Thomas ; Maurige, Jean-François ; Lallemand, Bernard ; Corillon, Patrick ; Bartoloméo, Joël ; Internationales, 8ème Floralies ; Gonzalez, Asier Perez ; Gonzalez-Foerster, Dominique ; Familiari, Christelle ; Kovacevic, Milomir ; Smith, Seton ; Boulcourt, Michel ; van der Keuken, Johan ; Belmont, Charles ; Tiberghien, Gilles A. ; Laurette, Matthieu ; Pflumm, Daniel ; Leroux, Pascal ; Strba, Annelies ; Geleynse, Wyn ; Baxter, Glen ; Weemans, Michel ; Barak, Ami
La nouvelle interlope 2, ERBAN - Ecole Régionale des Beaux-Arts de Nantes, 1999
Frans
boek